Quality of life, fatigue, and muscle strength in women with breast cancer undergoing chemotherapy or hormonal therapy: a case-control study - Silva, Naiany P.; Marques, Vitor A.; Ferreira-Junior, João B.; Freitas-Junior, Ruffo de; Vieira, Carlos A. (Frontiers in Oncology, 2025)
BackgroundBreast cancer treatments negatively affect women’s physical and emotional well-being due to adverse effects. This study compared the quality of life, fatigue levels, and muscle strength of women with breast cancer undergoing chemotherapy or hormonal therapy with a control group of healthy women.MethodsA case-control study was conducted including women aged 45 to 65 years diagnosed with breast cancer between October 2021 and August 2022 at the Hospital das Clínicas de Goiânia, Brazil. Approximately one age-matched control was selected from the general population for every 2.2 cases. Quality of life was assessed using the EORTC QLQ-BR23, fatigue with the FACT B + 4, and muscle strength through handgrip tests.ResultsNinety-five participants were included (65 cases, 30 controls). Among cases, 40% (n = 26) were undergoing chemotherapy and 60% (n = 39) hormonal therapy. Quality-of-life domains such as general symptoms, side effects, and arm and chest symptoms were worse among treated cases compared to controls (p < 0.01 for all). No significant differences were observed between treatment groups (p > 0.05). Fatigue levels were higher among cases compared to controls in domains such as physical and social well-being, general fatigue, cancer- related fatigue, and breast cancer-related fatigue (p < 0.01, p = 0.05, p < 0.01, p < 0.01, p < 0.01, respectively), with no significant differences between treatment groups (p > 0.05). Handgrip strength was lower in cases treated with hormonal therapy on the right side compared to controls (-5.0; 95% CI: -7.69 to -2.31; effect size: -0.49) which represents a moderate magnitude effect. On the left side, both treatment groups showed reduced strength compared to controls (-5.1; 95% CI: -7.99 to -2.21; -5.9; 95% CI: -8.51 to -3.29; effect sizes: -0.93 and -1.04, respectively) indicating effects of large magnitude, which may suggest possible clinical relevance. No significant differences were observed between treatment groups (p > 0.05).ConclusionDifferences in quality of life, fatigue, and muscle strength were observed between women undergoing treatment and those who were healthy, with no distinction between types of treatment.